Three-Dimensional Localization of the Smallest Capsid Protein in the Human Cytomegalovirus Capsid - Yu, Xuekui (American Society for Microbiology, 2005)
The smallest capsid proteins (SCPs) of the human herpesviruses differ substantially in size and sequence and are thought to impart some unique aspects of infection to their respective viruses. We used electron cryomicroscopy and antibody labeling to show that the 8-kDa SCP of human cytomegalovirus is attached only to major capsid protein subunits of the hexons, not the pentons. Thus, the SCPs of different herpesviruses illustrate that a protein can evolve significantly in sequence, structure, and function, while preserving its role in the architecture of the virus by binding to a specific partner in a specific oligomeric state.